Sustainable Practices in Nigerian Libraries: Exploring the Role of Green Libraries in Promoting Eco-Friendly Reading Spaces - Kolawole, Daniel; Oladokun, Bolaji (International Journal of Knowledge Content Development & Technology, 2025)
Green libraries are becoming pivotal in addressing environmental challenges while fostering sustainability in library services worldwide. However, Nigerian libraries lag in adopting green initiatives, despite the potential benefits for environmental conservation and community engagement. This paper explores the role of green libraries in promoting eco-friendly reading spaces in Nigeria, emphasizing the importance of sustainable building design, energy conservation, and resource management. The study discusses the global green library movement, highlighting examples from developed countries and identifying the specific challenges faced by Nigerian libraries. Key obstacles such as limited funding, inadequate infrastructure, and lack of awareness are examined in detail. Furthermore, the paper proposes strategies for overcoming these challenges, including capacity-building initiatives, policy reform, and collaborative efforts with both local and international organizations. By adopting green practices, Nigerian libraries can significantly reduce their ecological footprint, enhance public health, and contribute to the global agenda of sustainable development. The findings underscore the critical role of libraries in promoting environmental literacy and social responsibility, positioning them as hubs for sustainability education within their communities.